Light weight and fine‐grained access mechanism for secure access to outsourced data*. (14th August 2018) - Jahan, Mosarrat; Seneviratne, Suranga; Roy, Partha Sarathi; Sakurai, Kouichi; Seneviratne, Aruna; Jha, Sanjay
Summary: In this paper, we explore the problem of providing selective read/write access to the outsourced data for clients using mobile devices in an environment that supports users from multiple domains and where attributes are generated by multiple authorities. We consider Ciphertext‐Policy Attribute‐based Encryption (CP‐ABE) scheme as it can provide access control on encrypted outsourced data. One limitation of CP‐ABE is that the users can modify the access policy specified by the data owner if write operations are introduced in the scheme. We propose a protocol for providing different levels of access to outsourced data that permits the authorized users to perform write operation without altering the access policy specified by the data owner. Our scheme provides fine‐grained read/write access to the users, accompanied with a light weight signature scheme and computationally inexpensive user revocation mechanism suitable for resource‐constrained mobile devices. We provide a theoretical analysis of the security of the proposed protocol and the experimental results measured from a real‐world testbed.